PENGARUH MOTIVASI, BUDAYA KERJA, DAN KEPEMIMPINAN TERHADAP PRODUKTIVITAS PEGAWAI PEMERINTAH KABUPATEN NGANJUK - Anwar, Dinda Martalina; Sugiono, Sugiono; Purnomo, Hery (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The existence of a phenomenon in the secretariat office of the Nganjuk Regency government service found that there were some employees who still seemed to have low work motivation, there was a gap between employees and a lack of synergy between leaders and employees. The researcher aims to analyze the effect of motivation, work culture, and leadership on employee productivity at the Nganjuk Regency Government Service. The research method used by the researcher is quantitative with comparative causal technique. Samples were taken using probability sampling technique, obtained a sample of 58 respondents from a population of 139 employees of the Nganjuk government office secretariat. The research instrument used a closed questionnaire. The analysis technique uses multiple linear regression analysis with the prerequisite test for normality. The results showed that, partially proven there is a significant influence of motivation and leadership on employee productivity. While work culture is not partially proven to have a significant effect on employee productivity. The results of the simultaneous test of motivation, work culture, and leadership have a significant effect on the productivity of the Nganjuk Regency Government employees.